Pengaruh Ketidakadilan Gender Dan Implikasinya Dalam Keluarga - Rizqa Febry Ayu; Nadhilah Filzah (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2023)
Gender bias is an endless issue to be raised. It is motivated by the emergence of problems in various circles in society, academics, agencies to families. This is triggered by gender inequality itself and is caused by various factors. This study discusses how the influence of gender bias or injustice and its implications in the family. The method used is a literature review or library research, trying to explain and describe gender inequality and its effects in the household. Married couples should have a relationship that is horizontal and not vertical, this indicates that there is no superior and subordinate relationship but has an equal position under one unit, namely the family. However, factors such as marginalization, subordination, stereotypes, violence and other factors that are more profitable for one party make an influence and cause habituation or injustice within the smallest unit of society, namely the family.